Staggering Preventive Maintenance Actions at CMP Using a Dispatching Algorithm - Ramakrishnan, Srikanth; Chakravorty, Shiladitya; Tay, Jensen; Olsen, David; Zumpano, Peter (ASMC proceedings, 2020)
In a semiconductor fab, distributing wafers equally across a toolset (set of tools that perform similar operations) helps achieve a higher throughput as opposed to loading them unevenly. However, in some processing steps, level loading tools leads to uniform usage of consumables (material used up at a tool in processing wafers) and can trigger simultaneous Preventive Maintenance (PM) actions to replenish them. Managing simultaneous PMs with a small maintenance team reduces tool availability while using a bigger workforce entails higher costs. This study presents ways to overcome this situation by staggering PM actions across tools